Development of a Process for Low-Cost LFP Batteries Treatment - Rafaella-Aikaterini Megaloudi; Alexandros Galanis; Paschalis Oustadakis; Anthimos Xenidis (Materials Proceedings)
The recycling of lithium iron phosphate (LiFePO4) batteries from electric and hybrid vehicles was investigated, by applying mechanical pretreatment and hydrometallurgical methods. The aim was to extract lithium (Li) into the aqueous solution and precipitate iron (Fe) in the form of ferric iron phosphate (FePO4). Samples of lithium iron phosphate (LFP) batteries from small electric vehicles provided by the company BEEV were used in this study. Initially, the black mass was isolated using mechanical crushing, screening, and sink–float separation methods, avoiding the need for costly chemical or thermal treatments. The cathodic material was then leached with sulfuric acid (H2SO4) and hydrogen peroxide (H2O2) to oxidize ferrous to ferric iron, resulting in the precipitation of iron phosphate, which was collected in the solid residue from the leaching process. Leaching tests were conducted by varying the concentrations of sulfuric acid and hydrogen peroxide, as well as the leaching time. It has been indicated that by using a sulfuric acid concentration equal to the stoichiometric requirement, and hydrogen peroxide at four times the stoichiometric amount, Li extraction of greater than 98% was achieved within the first few minutes of leaching, while iron extraction remained below 0.5%.